2022
DOI: 10.1093/milmed/usab528
|View full text |Cite
|
Sign up to set email alerts
|

Defeated No More: Meaning-Making After Military Sexual Trauma

Abstract: Introduction Military sexual trauma (MST) has been a concern within our U.S. military for many years. Many interventions have been found to benefit this population, although meaning-based interventions are still lacking in this area. The purpose of this phenomenological study is to understand the meaning-making process and themes that arise for female military veterans as they narrate their experience(s) of MST. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…These results are in line with other studies that found that both forms of exposure to combat events are associated with higher PTSS and PTG (Evans et al, 2018; Greenberg et al, 2021). Our results do not echo the studies that found that experiences of MST are associated with higher odds for PTSS (Sumner et al, 2021) and PTG (Preston et al, 2023). It is possible that the qualitative methodology of the one study that linked MST to PTG among female combatants (Preston et al, 2023), which is different than our quantitative methodology and, specifically, the LPA, contributed to this pattern of findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are in line with other studies that found that both forms of exposure to combat events are associated with higher PTSS and PTG (Evans et al, 2018; Greenberg et al, 2021). Our results do not echo the studies that found that experiences of MST are associated with higher odds for PTSS (Sumner et al, 2021) and PTG (Preston et al, 2023). It is possible that the qualitative methodology of the one study that linked MST to PTG among female combatants (Preston et al, 2023), which is different than our quantitative methodology and, specifically, the LPA, contributed to this pattern of findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, exposure to combat events (Greenberg et al, 2021) and total potentially morally injurious events (PMIEs) were associated with PTSS (Zerach & Levi‐Belz, 2022b). However, exposure to MST was also associated with high PTG (Preston et al, 2023), and exposure to PMIEs perpetrated by oneself was associated with high PTG (Evans et al, 2018). Given the different types of military‐related exposure and heterogeneity in reactions to PTEs, it is important to understand the factors that contribute to each constellation of PTSS and PTG experienced by women veterans and the possible positive psychological outcomes of such constellations.…”
Section: Introductionmentioning
confidence: 99%